Coping With Anxiety: Brain Structural Correlates of Vigilance and Cognitive Avoidance - Günther, Vivien; Jahn, Salome; Webelhorst, Carolin; Bodenschatz, Charlott Maria; Bujanow, Anna; Mucha, Simone; Kersting, Anette; Hoffmann, Karl-Titus; Egloff, Boris; Lobsien, Donald; Suslow, Thomas (Frontiers in Psychiatry, 2022)
Background: Individuals differ in their dispositional coping behavior when they are confronted with anxiety-provoking situations. Cognitive avoidance is characterized by a withdrawal from threatening information, whereas vigilance denotes the intensive search for threat-related information. Functional neuroimaging studies indicate alterations in brain responsivity to emotional stimuli as a function of cognitive avoidant and vigilant coping, but findings are partially discrepant. Studies on structural correlates of coping styles are scarce. Materials and Methods: By using structural magnetic resonance imaging, the present study examined the relationship between brain gray matter volume and coping strategies in 114 healthy individuals. Individual differences in vigilance and cognitive avoidance were measured by the Mainz Coping Inventory. Results: Exploratory whole-brain analyses were conducted. Cognitive avoidant coping significantly predicted reduced gray matter volume in the bilateral thalamus, whereas vigilant coping was associated with volumetric increases in the bilateral thalamus. These relationships remained significant when controlling for a potential influence of age, sex, depressive symptoms, and trait anxiety. Discussion: Our findings indicate that dispositional strategies to deal with anxiety-provoking situations are related to volumetric alterations in the thalamus, a brain structure that has been implicated in the mediation of attentional processes and alertness, and the anticipation of harm. The dispositional tendency to monitor the environment for potential threats (i.e., vigilance), appears to be associated with volumetric increases in the thalamus, whereas the dispositional inclination to divert one’s attention away from distressing stimuli (i.e., cognitive avoidance) seems to go along with reductions in thalamic gray matter density.